Influence of clay mineralogy on undrained shear strength using Fall cone test - Eyyüb Karakan (Građevinar, 2023)
Consistency limits are the basic parameters used as standard inputs for any soil investigation program to evaluate the geotechnical properties of fine-grained soils. The primary objective of this study is to investigate the variations in the undrained shear strength of clays with different plasticity properties based on the fine content, clay mineralogy, and water absorption capacity. To achieve this objective, 33 Fall cone tests were conducted on low-, high-, and very high-plastic clay mixtures. Various blends of different plasticity were ensured by preparing mixtures of Na-montmorillonite (NaM)/Ca-montmorillonite (CaM), Na-montmorillonite (NaM)/Kaolinite (K), and Na-montmorillonite (NaM)/Sepiolite (S). According to the experimental results, the highest liquid limit (LL) was obtained in 100 % NaM clay at 255.07 %, whereas the lowest LL was obtained in 100 % S clay at 33.55 %. Similarly, the highest undrained shear strength was obtained at 160 kPa at 30 % water content in the 100 % NaM clay, whereas the lowest undrained shear strength was obtained at 10 kPa in the 100 % S clay at the same water content. Consequently, based on an experimental framework, empirical equations were obtained which could be used to establish the relationships among cone penetration-water content, liquid limit-clay content, and undrained shear strength-cone penetration.